2012
DOI: 10.1371/journal.pone.0032211
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Functional Selectin Ligand Interactions Compromises Long Term Tumor Protection by CD8+ T Cells

Abstract: Central memory CD8+ T cells expressing the adhesion molecule CD62L (L-selectin) are potent mediators of anti-cancer immunity due to their ability to proliferate extensively upon antigen re-stimulation. The interaction of selectin with its ligands mediates leukocyte rolling along high endothelial venules. Mice deficient in α(1,3) Fucosyltransferase IV and VII (FtDKO) lack functional L, P and E selectin ligands. Thus, we addressed whether the lack of selectin ligand interactions alters tumor protection by CD8+ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
2
11
0
1
Order By: Relevance
“…Functional selectin ligand deficiency results in elevated leukocyte levels in circulation, attributed in part to reduced neutrophil turnover . Consistent with our previous study, our data presented above show that enlarged splenic sizes in naive FtDKO mice is associated with increased cell numbers compared to their WT counterparts (Figure A and B) . A similar trend was observed between WT and FtDKO mice at day 3 postinfection with LM 10 4 CFUs i.v.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Functional selectin ligand deficiency results in elevated leukocyte levels in circulation, attributed in part to reduced neutrophil turnover . Consistent with our previous study, our data presented above show that enlarged splenic sizes in naive FtDKO mice is associated with increased cell numbers compared to their WT counterparts (Figure A and B) . A similar trend was observed between WT and FtDKO mice at day 3 postinfection with LM 10 4 CFUs i.v.…”
Section: Resultssupporting
confidence: 91%
“…Taken together, we show that innate immune responses sufficiently controlled bacterial numbers despite impaired lymphocyte homing in our acute infection model. However, it is important to note that adaptive immune responses mediated by lymphocytes are not dispensable during LM infection . We previously showed that sterilizing immunity to LM was mediated by antigen‐specific CD8 + T cells as well upon infection rechallenge .…”
Section: Discussionmentioning
confidence: 99%
“…Higher vascular E-selectin expression among Merkel cell carcinomas in different patients was associated with larger numbers of CD8 T-cells, although it is unclear if the infiltrating T-cells were ESL + (Afanasiev et al, 2013). Fucosyltransferase IV and VII knockout CD8 T-cells cannot generate the carbohydrate structure to form functional ESL (Goelz et al, 1994, 1990; Knibbs et al, 1996; Maly et al, 1996) and their entry into SC B16-cOVA tumors is reduced compared to wild-type cells (Stark et al, 2012). However, whether wild-type CD8 T-cell entry was dependent on either ESL or PSL (which is also fucosyltransferase dependent) or both was not determined.…”
Section: Determinants Of Cd8 T-cell Representation In Tumors Andmentioning
confidence: 99%
“…Previously, we have shown that when memory OVA-specific CD8 + T cell frequencies are similar and CD62L expression is low or their ligand is absent, long lasting tumor protection is impaired [26,35]. At late time points (>200 days) after a single dose of MS-OVA or LM-OVA, a low frequency of OVA-specific CD8 + T cells remain (~0.1%) and they are predominantly CD62L high .…”
Section: Discussionmentioning
confidence: 99%